Helical springs for watch movements
By using ternary alloys composed of elements such as niobium, titanium and Zr/Hf, the problems of long settling time and material brittleness of Nb-Ti alloys are solved, and a more efficient production process and more stable coil spring performance are achieved.
Patent Information
- Application Number
- CN202210251472.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-16
- Filing Date
- 2022-03-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-03-15
AI Technical Summary
The existing Nb-Ti binary alloys used in clock coil springs have a long precipitation time during the setting process, and a high proportion of titanium leads to brittleness of the material, difficult to deform, and affects manufacturing efficiency and product performance.
A at least ternary alloy composed of elements such as niobium, titanium and Zr/Hf is used to partially replace Ti with Zr and/or Hf, and the α phase precipitation is accelerated by heat treatment to form a stable microstructure.
It shortens the shaping time of the coil spring, reduces secondary errors in the production process, and improves the fatigue resistance and stability of the material. It is suitable for use in high-precision watch movement balance wheels.
Abstract
Description
Technical Field
[0001] The present invention relates to a spiral spring used for equipping a balance wheel of a clock movement and also relates to a method for manufacturing the spiral spring. Background Art
[0002] The manufacture of spiral springs for watchmaking has to face constraints that are often incompatible at first glance:
[0003] - Need to obtain a high elastic limit,
[0004] - easy to manufacture, especially drawing and rolling,
[0005] - Excellent fatigue resistance,
[0006] - stable performance over time,
[0007] - Small cross section.
[0008] The alloy selected for the helical spring must also have properties that guarantee that the chronometric performance is maintained despite the temperature variations in use of the timepiece into which this helical spring is introduced. The thermoelastic coefficient of the alloy, also known as TEC, is of great significance here. In order to form a chronometric oscillator with a CuBe or nickel-silver balance, a TEC of + / -10 ppm / °C must be achieved. The formula relating the TEC of the alloy to the expansion coefficient of the helix (α) and the expansion coefficient of the balance (β) is as follows:
[0009]
[0010] The variables M and T are the ratio in s / d and the temperature in °C, respectively. E is the Young's modulus of the coil spring, where (1 / E.dE / dT) is the TEC of the coil alloy and the coefficient of expansion is in °C. -1 express.
[0011] In practice, TC is calculated between 8°C and 38°C as follows:
[0012]
[0013] Its value must be between -0.6 and +0.6 s / d°C.
[0014] A spiral spring known from the prior art for making a watch is made of a binary Nb-Ti alloy, wherein the percentage of Ti is generally between 40 and 60% by weight, more particularly 47%. With the aid of an adapted deformation and heat treatment scheme (diagram), this spiral spring has a two-phase microstructure, comprising niobium in the β phase and titanium in the form of precipitates in the α phase. The cold-worked alloy in the β phase has a strong positive TEC, while the precipitation of the α phase, which has a strong negative TEC, brings the TEC of the two-phase alloy close to zero, which is particularly advantageous for TC.
[0015] However, there are some disadvantages when using Nb-Ti binary alloys for coil springs.
[0016] One disadvantage of binary Nb-Ti alloys is related to the precipitation of titanium, which mainly occurs during the fixing step after the coiling step. In practice, the precipitation time is very long, ranging from 8 to 30 hours for NbTi47 alloys and about 20 hours on average, which significantly increases the production time.
[0017] Besides the problem of long production times, too high a proportion of titanium leads to the formation of a brittle martensitic phase, which makes it difficult, if not impossible, to deform the material, and thus makes the material unsuitable for the manufacture of helical springs. It is therefore advisable not to add too much titanium to the alloy.
[0018] To date, there is still a need to develop new chemical compositions that meet the various criteria of the absence of brittle phases and reduced production time for manufacturing coil springs. Summary of the invention
[0019] The object of the present invention is to propose a new chemical composition of a helical spring capable of overcoming the above-mentioned disadvantages.
[0020] To this end, the invention relates to a spiral spring for a watch made of at least a ternary alloy based on niobium and titanium. According to the invention, Ti is partially replaced by Zr and / or Hf, which can also form alpha-phase precipitates. The partial replacement of Ti by Zr and / or Hf makes it possible to accelerate precipitation during shaping and thus reduce production time.
[0021] More particularly, the present invention relates to a helical spring for equipping a balance wheel of a timepiece movement, said helical spring being made of at least a ternary alloy consisting of the following components:
[0022] - Nb, Ti and at least one element selected from Zr and Hf,
[0023] - optionally at least one element selected from W and Mo,
[0024] - possible other trace elements selected from O, H, C, Ta, Fe, N, Ni, Si, Cu, Al,
[0025] The weight percentages are as follows:
[0026] - Nb content ranges from 40% to 84%,
[0027] - the total content of Ti, Zr and Hf is 16% to 55%, wherein the minimum content of Ti is preferably 15%,
[0028] - W and Mo contents are 0 to 2.5% respectively,
[0029] - the content of each of said elements selected from O, H, C, Ta, Fe, N, Ni, Si, Cu, Al is from 0 to 1600 ppm, wherein the sum of said trace amounts is less than or equal to 0.3% by weight.
[0030] The present invention also relates to a method for manufacturing the watch spiral spring, which method comprises in sequence:
[0031] - a step of manufacturing or providing a billet made of at least a ternary alloy consisting of:
[0032] - Nb, Ti and at least one element selected from Zr and Hf,
[0033] - optionally at least one element selected from W and Mo,
[0034] - possible other trace elements selected from O, H, Ta, C, Fe, N, Ni, Si, Cu, Al,
[0035] The weight percentages are as follows:
[0036] ᴑ Nb content is 40% to 84%,
[0037] ᴑ The total content of Ti, Zr and Hf is 16% to 55%, of which the minimum content of Ti is preferably 15%,
[0038] ᴑ The contents of W and Mo are 0 to 2.5%, respectively.
[0039] ᴑ The content of each of the elements selected from O, H, Ta, C, Fe, N, Ni, Si, Cu, Al is 0 to 1600 ppm, wherein the sum of the trace amounts is less than or equal to 0.3 wt.%,
[0040] - a step of beta-quenching the blank so that the alloy has titanium substantially in the form of a solid solution, niobium in the beta phase, and zirconium and / or hafnium also substantially in the form of a solid solution,
[0041] - a step of subjecting said alloy to a series of deformation steps followed by intermediate heat treatments,
[0042] - a winding step to form a helical spring,
[0043] - The final heat treatment step, also called shaping.
[0044] Advantageously, the last heat treatment step, which finally completes the precipitation of titanium and zirconium and / or hafnium, is carried out at a holding temperature of 400 to 600° C. for a period of 4 to 8 hours.
[0045] In addition to reducing the setting time, partial replacement of titanium with zirconium can also reduce secondary errors, as explained below. DETAILED DESCRIPTION
[0046] The invention relates to a timepiece helical spring made from at least a ternary alloy comprising niobium and titanium and one or more additional elements.
[0047] According to the present invention, the alloy consists of the following components:
[0048] - Nb, Ti and at least one element selected from Zr and Hf,
[0049] - optionally at least one element selected from W and Mo,
[0050] - possible other trace elements selected from O, H, C, Ta, Fe, N, Ni, Si, Cu, Al,
[0051] The weight percentages are as follows:
[0052] ᴑ Nb content is 40% to 84%,
[0053] ᴑ The total content of Ti, Zr and Hf is 16% to 55%,
[0054] ᴑ The contents of W and Mo are 0 to 2.5%, respectively.
[0055] ᴑ The content of each of said elements selected from O, H, C, Ta, Fe, N, Ni, Si, Cu, Al is from 0 to 1600 ppm, wherein the sum of said trace amounts is less than or equal to 0.3 wt.%.
[0056] Preferably, the weight content of Nb is greater than 45%, or even greater than or equal to 50%, in order to obtain a sufficient percentage of the β phase with a strong positive TEC intended to compensate for the negative TEC of the α phase of Ti, Zr, Hf.
[0057] Preferably, the Ti content is kept at a minimum content of 15% by weight, because Ti is more economical than Zr and Hf. In addition, it has the advantage of a lower melting temperature than Zr and Hf, which facilitates casting.
[0058] The weight percentage of oxygen is less than or equal to 0.10% of the total amount, or even less than or equal to 0.085% of the total amount.
[0059] The weight percentage of hydrogen is less than or equal to 0.01% of the total amount, in particular less than or equal to 0.0035% of the total amount, or even less than or equal to 0.0005% of the total amount.
[0060] The weight percentage of carbon is less than or equal to 0.04% of the total amount, in particular less than or equal to 0.020% of the total amount, or even less than or equal to 0.0175% of the total amount.
[0061] The weight percentage of tantalum is less than or equal to 0.10 weight % of the total amount.
[0062] The weight percentage of iron is less than or equal to 0.03% of the total amount, in particular less than or equal to 0.025% of the total amount, or even less than or equal to 0.020% of the total amount.
[0063] The weight percentage of nitrogen is less than or equal to 0.02% of the total amount, in particular less than or equal to 0.015% of the total amount, or even less than or equal to 0.0075% of the total amount.
[0064] The weight percentage of nickel is less than or equal to 0.01% of the total amount.
[0065] The weight percentage of silicon is less than or equal to 0.01% of the total amount.
[0066] The weight percentage of copper is less than or equal to 0.01% of the total amount, in particular less than or equal to 0.005% of the total amount.
[0067] The weight percentage of aluminum is less than or equal to 0.01% of the total amount.
[0068] According to the invention, Ti is partially replaced by Zr and / or Hf, forming α precipitates like Ti, thereby accelerating precipitation during shaping and thus reducing production time. Advantageously, the sum of the Zr and Hf contents is 1 to 40 wt %. Preferably, the sum of the Zr and Hf contents is 5 to 25 wt %, more preferably 10 to 25 wt %, and even more preferably 15 to 25 wt %.
[0069] Advantageously, Ti is at least replaced by Zr, which also allows to reduce the quadratic error, which is a measure of the curvature of the ratio that is usually approximated by a straight line through two points (8°C and 38°C). Binary alloys Nb-Ti with a Ti weight percentage of 47% (NbTi47) and binary alloys Nb-Zr with a Zr weight percentage ranging from 0 to 70% were tested to show the influence of Ti and Zr on the quadratic error, respectively. The quadratic error is measured at 23°C. It is the difference of the ratio at 23°C with respect to the straight line connecting the ratios at 8°C and 38°C. For example, the ratios at 8°C, 23°C and 38°C can be measured using a device of the Witschi chronograph type.
[0070] Table 1 below shows data for Nb-Zr alloys, pure Nb and NbTi47 alloy as a function of the weight percentage of Zr. The quadratic error of pure Nb at 23°C is -6.6 s / d. The precipitation of Ti in the NbTi47 alloy compensates for the negative effect of Nb, but its positive value rises excessively, reaching 4.5 s / d. On the other hand, the Nb-Zr alloy has a negative quadratic error when the Zr content is greater than 0%, or even zero when the Zr content is greater than or equal to 45% by weight. Therefore, the partial replacement of Ti with Zr in the ternary alloy can compensate for the overly positive effect of Ti on the quadratic error. Compared with the binary NbTi47 alloy, the addition of a few weight percent of Zr can already reduce the quadratic error to a value close to 0. Therefore, advantageously, the Zr content is at least 5 weight percent.
[0071] alloy weight% Secondary error at 23°C Pure Niobium 0% -6.6 s / d NbTi47 47% 4.5 s / d <![CDATA[Nb 30 Zr 70 ]]> 70% -0.2 s / d <![CDATA[Nb 45 Zr 55 ]]> 55% 0.0 s / d <![CDATA[Nb 50 Zr 50 ]]> 50% 0.2 s / d <![CDATA[Nb 55 Zr 45 ]]> 45% 0.0 s / d <![CDATA[Nb 60 Zr 40 ]]> 40% -3.0 s / d <![CDATA[Nb 65 Zr 35 ]]> 35% -4.1 s / d <![CDATA[Nb 70 Zr 30 ]]> 30% -4.8 s / d <![CDATA[Nb 80 Zr 20 ]]> 20% -5.0 s / d <![CDATA[Nb 85 Zr 15 ]]> 15% -5.8 s / d <![CDATA[Nb 90 Zr 10 ]]> 10% -6.0 s / d <![CDATA[Nb 100 ]]> 0% -6.6 s / d
[0072] Table 1.
[0073] The alloy may also contain W and Mo in a content of 0 to 2.5% by weight each, in order to increase the Young's modulus of the alloy, which allows reducing the thickness of the spiral for a given torque of the spring and thus making it lighter.
[0074] Advantageously, the helical spring according to the invention has a multiphase microstructure comprising a body-centered cubic β phase of niobium and a single α phase of titanium and zirconium and / or hafnium.
[0075] In order to obtain such a microstructure, in the manufacturing method, during the process of shaping the spring, heat treatment is required to finally complete the precipitation of the α phase. The manufacturing method sequentially performs the following steps:
[0076] - A step of providing or manufacturing a blank. For example, the blank may be manufactured by melting the elements in an electric arc furnace or an electron gun furnace to form a blank or ingot which is hot forged and then cold deformed and heat treated between deformation stages. The blank is made of at least a ternary alloy consisting of the following components:
[0077] - Nb, Ti and at least one element selected from Zr and Hf,
[0078] - optionally at least one element selected from W and Mo,
[0079] - possible other trace elements selected from O, H, Ta, C, Fe, N, Ni, Si, Cu, Al,
[0080] The weight percentages are as follows:
[0081] ᴑ Nb content is 40% to 84%,
[0082] ᴑ The total content of Ti, Zr and Hf is 16% to 55%,
[0083] ᴑ The contents of W and Mo are 0 to 2.5%, respectively.
[0084] ᴑ The content of each of the elements selected from O, H, Ta, C, Fe, N, Ni, Si, Cu, Al is 0 to 1600 ppm, wherein the sum of the trace amounts is less than or equal to 0.3 wt.%,
[0085] - a step of beta-quenching the blank so that the alloy has titanium substantially in the form of a solid solution, niobium in the beta phase, and zirconium and / or hafnium also substantially in the form of a solid solution,
[0086] - A series of deformation steps followed by intermediate heat treatments are applied to the alloy. Deformation refers to deformation carried out by wire drawing and / or rolling. If necessary, wire drawing may require the use of one or more dies during the same step or during a different step. Wire drawing is carried out until a wire with a circular cross section is obtained. Rolling can be carried out in the same deformation step as wire drawing or in a separate step. Advantageously, the last step applied to the alloy is rolling, preferably rolling to have a rectangular profile compatible with the entry cross section of the winding pin.
[0087] - a winding step to form a helical spring,
[0088] - Final heat treatment step.
[0089] In these coupled deformation-heat treatment steps, each deformation is performed with a given deformation amount of 1 to 5, which corresponds to the general formula 2ln(d0 / d), where d0 is the diameter of the last beta quench and where d is the diameter of the cold-worked wire. The total accumulation of deformations throughout this series of steps brings a total deformation amount of 1 to 14. Each coupled deformation-heat treatment step each includes a heat treatment of the α phase that precipitates Ti, Zr and / or Hf.
[0090] The beta quenching prior to the deformation and heat treatment steps is a solution treatment at a temperature of 700°C to 1000°C for 5 minutes to 2 hours under vacuum, followed by cooling in gas.
[0091] Even more particularly, this beta quench is a solution treatment at 800° C. for 1 hour under vacuum, followed by cooling in gas.
[0092] Returning to the paired deformation-heat treatment process, the heat treatment is a precipitation treatment at a temperature of 300° C. to 700° C. for a duration of 1 to 200 hours. More specifically, at a temperature of 400° C. to 600° C. for a duration of 3 to 30 hours.
[0093] More particularly, the method comprises one to five paired deformation-heat treatment steps.
[0094] More particularly, the first coupled deformation-heat treatment step comprises a first deformation with a reduction in cross-sectional area of at least 30%.
[0095] More particularly, each paired deformation-heat treatment process, except the first one, includes a deformation in which the cross-sectional area is reduced by at least 25% between the two heat treatments.
[0096] More particularly, after manufacturing the alloy billet and before the deformation-heat treatment process, in an additional step, a surface layer of ductile material is added to the billet to facilitate forming into a wire shape during deformation, the ductile material being selected from copper, nickel, copper-nickel, copper-manganese, gold, silver, nickel-phosphorus Ni-P and nickel-boron Ni-B, etc. And after the deformation-heat treatment process or after the winding step, the ductile material layer is stripped from the wire, in particular by chemical etching.
[0097] Alternatively, a surface layer of ductile material is deposited to form a helical spring whose pitch is not a multiple of the thickness of the blade. In another variant, a surface layer of ductile material is deposited to form a spring whose pitch is variable.
[0098] In a particular watchmaking application, ductile material or copper is therefore added at a given moment to facilitate shaping into the wire shape, so that a thickness of 10 to 500 microns remains on the wire with a final diameter of 0.3 to 1 millimeter. The ductile material or copper layer is stripped from the wire in particular by chemical etching and then flattened before the actual spring is made by winding.
[0099] The supply of ductile material or copper may be electroplated or may be mechanical and then formed into a sheath or tube of ductile material or copper which is conditioned over a large diameter alloy rod and then thinned in a deformation step of the composite rod.
[0100] The removal of this layer can be carried out in particular by chemical etching using solutions based on cyanide or on acids such as nitric acid.
[0101] The final heat treatment is carried out at a temperature between 300° C. and 700° C. for a duration of 1 to 200 hours. More particularly, at a temperature between 400° C. and 600° C. for a duration of 3 to 30 hours. Advantageously, the duration is between 4 and 8 hours, maintained at a temperature between 400° C. and 600° C. During the final heat treatment, the precipitation of titanium in the alpha phase and of hafnium and / or zirconium is finally completed.
[0102] By a suitable combination of deformation and heat treatment steps, a very fine microstructure can be obtained, which is in particular nanostructured, comprising beta niobium and alpha phases of titanium and hafnium and / or zirconium. This alloy combines a very high elastic limit greater than at least 500 MPa, an elastic modulus greater than or equal to 100 GPa and preferably greater than or equal to 110 GPa. This combination of properties is very suitable for helical springs. In addition, this at least ternary niobium-titanium-hafnium and / or zirconium alloy according to the invention can be easily covered with ductile materials or copper, which greatly facilitates its deformation by wire drawing.
[0103] This alloy also has an "Elinvar"-like effect, with a thermoelastic coefficient of almost zero in the temperature range commonly used in watches, and is suitable for the manufacture of self-compensating spirals.
Claims
1. A spiral spring for equipping a balance wheel of a watch movement, characterized in that The coil spring is made of an alloy consisting of the following components: - Nb, Ti and at least one element selected from Zr and Hf, - optionally at least one element selected from W and Mo, - optional other trace elements selected from O, H, Ta, C, Fe, N, Ni, Si, Cu, Al, The weight percentages are as follows: -Nb content of 40% to 84%, - the total content of Ti, Zr and Hf is 16% to 55%, wherein the Ti content is greater than or equal to 15% by weight, the sum of the contents of Zr and Hf is 10 to 25% by weight, -W and Mo contents are 0 to 2.5%, respectively, - the content of each of the elements selected from O, H, Ta, C, Fe, N, Ni, Si, Cu, Al is 0 to 1600 ppm, wherein the sum of the trace amounts is less than or equal to 0.3% by weight, The coil spring has a microstructure including β-phase Nb, α-phase Ti, and Zr and / or Hf.
2. Helical spring according to the preceding claim, characterized in that The Nb content is greater than 45 wt%.
3. The coil spring according to claim 1 or 2, characterized in that: The sum of the contents of Zr and Hf is 15 to 25% by weight.
4. The coil spring according to claim 1 or 2, characterized in that: It contains at least 5% by weight of Zr.
5. The coil spring according to claim 1 or 2, characterized in that: It contains Zr and Hf.
6. The coil spring according to claim 1 or 2, characterized in that: It has an elastic limit greater than or equal to 500 MPa, and an elastic modulus greater than or equal to 100 GPa.
7. The coil spring according to claim 6, characterized in that It has an elastic modulus greater than or equal to 110 GPa.
8. A method for manufacturing a spiral spring for assembling a balance wheel of a watch movement, characterized in that: They include, in order: - A step of providing a billet made of at least a ternary alloy consisting of: - Nb, Ti and at least one element selected from Zr and Hf, - optionally at least one element selected from W and Mo, - optional other trace elements selected from O, H, Ta, C, Fe, N, Ni, Si, Cu, Al, The weight percentages are as follows: Nb content is 40% to 84%, The total content of Ti, Zr and Hf is 16% to 55%, wherein the Ti content is greater than or equal to 15% by weight, and the sum of the contents of Zr and Hf is 10 to 25% by weight, The contents of W and Mo are 0 to 2.5%, respectively. The content of each of the elements selected from O, H, Ta, C, Fe, N, Ni, Si, Cu, Al is 0 to 1600 ppm, wherein the sum of the trace amounts is less than or equal to 0.3 wt %, - a step of beta-quenching the blank so that the alloy has titanium substantially in the form of a solid solution, niobium in the beta phase, and zirconium and / or hafnium also substantially in the form of a solid solution, - a step of subjecting said alloy to a series of deformation steps followed by intermediate heat treatments, - a winding step to form a helical spring, - Final heat treatment step.
9. The method for manufacturing a coil spring according to claim 8, characterized in that: The beta quenching is a solution treatment in which the temperature is 700° C. to 1000° C. under vacuum for a duration of 5 minutes to 2 hours, followed by cooling in gas.
10. The method for manufacturing a coil spring according to claim 8 or 9, characterized in that: The beta quenching is a solution treatment at 800°C under vacuum for 1 hour, followed by cooling in gas.
11. The method for manufacturing a coil spring according to claim 8 or 9, characterized in that: The final heat treatment and the intermediate heat treatments of each step are precipitation treatments of α-phase Ti and Zr and / or Hf, and are carried out at a holding temperature of 300° C. to 700° C. for a duration of 1 hour to 200 hours.
12. The method for manufacturing a coil spring according to claim 8 or 9, characterized in that: The final heat treatment is performed at a holding temperature of 400° C. to 600° C. for a duration of 4 to 8 hours.
13. The method for manufacturing a coil spring according to claim 8 or 9, characterized in that: After the step of providing the alloy billet and before the step of applying a series of deformation steps, a surface layer of ductile material is added to the billet to facilitate forming into a wire shape, the ductile material being selected from copper, nickel, copper-nickel, copper-manganese, gold, silver, nickel-phosphorus Ni-P and nickel-boron Ni-B, and the surface layer of ductile material is stripped from the wire by chemical etching before or after the winding step.
Citation Information
Patent Citations
Spiral timepiece spring
CN109116712A
Coil spring for timepiece movement
CN115079543A
Timepiece and spring thereof
US20070133355A1